Interview with Dr. Joan Pagès Blanch. Didactics of Social Sciences and formation of teachers. - Pagés Blanch, Joan (2016)
The interview with Dr. Joan Pagés Blanch addresses topics related to the teaching of Social Sciences and teacher training. Dr. Pagés introduces important topics such as the role of teachers in the curriculum and their training to face the challenges that this field entails. It indicates that one of the challenges of the didactics of social disciplines, geography and history is to teach future teachers how to construct criteria for the selection and sequencing of social, geographical and historical school contents. It also addresses the theme of the study plans and discusses the question How to teach History in the XXI century?